Potentiation of Opsonization and Phagocytosis of Streptococcus pyogenes following Growth in the Presence of Clindamycin - Gemmell, Curtis G. (1981)
Streptococcus pyogenes, bearing M-protein on its surface, resists opsonization by normal human serum and subsequent phagocytosis by human polymorphonuclear leukocytes. Previous studies have shown that M-protein positive organisms are poorly opsonized by the alternate pathway of complement. In an attempt to define further the role of the surface components of S. pyogenes in this process, we examined the ability of clindamycin, an antibiotic that inhibits protein biosynthesis, to alter bacterial opsonization. An M-protein positive strain of S. pyogenes was grown in varying concentrations of clindamycin at levels lower than those which inhibited growth, i.e., at levels less than the minimal inhibitory concentration. These bacteria were incubated with purified human polymorphonuclear leukocytes and peripheral blood monocytes. Significant enhancement of bacterial opsonization, phagocytosis, and killing resulted. Measurement of complement consumption and binding of the third component of complement (C3) onto the bacterial surface demonstrated that organisms grown in the presence of clindamycin activated complement more readily and fixed more C3 on their surface. Electron microscopy revealed the probable basis for these findings. Streptococci exposed to clindamycin during growth were largely denuded of surface “fuzz,” the hairlike structures bearing M-protein. We conclude that the incorporation of clindamycin at concentrations that fail to inhibit growth of S. pyogenes nevertheless causes significant changes in the capacity of these bacteria to resist opsonization by serum complement. These findings support the hypothesis that M-protein inhibits bacterial opsonization by interfering with effective complement activation on the bacterial surface.